Determination of the optimal ejaculate concentration of a buffalo bull for successful semen cryopreservation - Bansal, Krishna; Jhamb, Dinesh; Yadav, Usha; Meel, Mamta; Gupta, Akanksha; Bala, Renu; Virmani, Meenakshi; Punetha, Meeti; Kumar, Dharmendra; Kumar, Pradeep (Frontiers in Veterinary Science, 2025)
For cattle bulls, only ejaculates with a sperm concentration of 500 million/mL or higher are selected for sperm cryopreservation. There is no established ejaculate’s minimum sperm concentration threshold for buffalo semen cryopreservation. Therefore, the first objective of the study was to determine the percentage of ejaculates of buffalo bulls having concentrations lower than 500 million/mL, the percentage of ejaculates suitable for cryopreservation across different concentrations of donated ejaculates, and to estimate the impact of ejaculate concentrations on the production of semen doses. The second objective was to evaluate the post-thaw sperm quality of ejaculates that initially met the criteria for cryopreservation. After analyzing 5,347 ejaculates from 31 buffalo bulls, it was found that 9.96% of the buffalo semen ejaculates had a sperm concentration of less than 500 million/mL. Of these, 48% qualified the minimum criteria, mainly based on sperm motility. The maximum semen doses (8.79%) were produced by the ejaculates with a sperm concentration between 1,101 and 1,201 million/mL. For the second objective of the study, the ejaculates were categorized into four groups: <300, 300–400, >400- < 500, and ≥ 500 million sperm/mL, diluted to a final concentration of 80 million sperm/mL and cryopreserved. The frozen–thawed sperm of different groups were evaluated by a computer-assisted sperm analyser (CASA) and a flow cytometer. Remarkably, it was found that sperm motility, integrity of plasma and acrosome membrane, and mitochondrial membrane potential (MMP) significantly decreased (p < 0.05) when the ejaculates of category <300 were cryopreserved, despite being qualified in subjective motility analysis compared to the other categories. Except for the category <300, in all the other three categories, there was no significant difference (p > 0.05) in the percentage of spermatozoa in MMP. The highest and lowest percentages of spermatozoa with high mitochondrial superoxide were found in categories <300 and ≥500, respectively. In conclusion, buffalo semen ejaculates with a concentration greater than 300 million sperm/mL should be considered for cryopreservation.